Pengaruh Kepemimpinan dan Kemampuan Manajerial Kepala Sekolah Terhadap Kinerja Guru di Sekolah Menengah Kejuruan (SMK) Negeri Kabupaten Seram Bagian Timur - Rumeon, M. Sidik; Papilaya, P.; Rahabav, P.; Rumfot, Sumarni (LP. Ma'arif Janggan Magetan, 2024)
The Influence of School Principals' Leadership and Managerial Skills on Teachers' Performance at SMK Negeri Kabupaten Seram Bagian Timur” Given the increasingly complex challenges in the field of vocational education, the role of the principal as a leader and manager becomes crucial for enhancing teacher performance effectiveness. The research method used is a quantitative approach with a survey instrument (questionnaire). Data were collected using a questionnaire distributed to 105 teachers in State Vocational High Schools in Seram Bagian Timur Regency and analyzed using descriptive and inferential analysis. The variables studied include independent variables, namely Principal Leadership (X1) and Principal Managerial Ability (X2), and the dependent variable, which is Teacher Performance (Y)